(3GdZQjHs - (3cGej, GdHjQs; (3SYO, Wg YHO GdQDhas; (3eMehO, cQjes ((3GdbGgQIs (3OGQGdcJGH GdYQHjs, 2014)
(3jJMOK GdcJGH Yf TNUjI eHQSh GdYHKj GdPj jYjT Ydj gGeT GdeLJeY hdg bfGYg Ydj gGeT GdeLJeY h dg eYJbOGJg GdNGUg hgh jSGb Gdj SGMI GdeMceI adG jYQa HeGPG jLjH hdGeGPG jfJXQg acd TF eJSGh dOjgs
(3bUU YQHjs
(3GdfU eJQLe Gdi GddZI GdYQHjI ef GddZg GdaQfSjIs
1 11 13
Keywords: (3GdCOH GdaQfSjs; (3GdeJQLeGJs